Bestuursfaktore wat die werkstevredenheid van hoofde van sekondêre skole in die Noord-Kaapprovinsie beïnvloed / Hendrik van der Poll Kirsten - Kirsten, Hendrik Van der Poll (Potchefstroom University for Christian Higher Education, 2013)
The aim of this research is threefold: • to determine the nature of job satisfaction; • to determine the factors which influence the job satisfaction of principals at secondary schools; and • to determine which factors influence the job satisfaction of principals at secondary schools in practice. In order to achieve these aims a literature study and empirical study were undertaken. The literature study was based on primary and secondary sources. A DIALOG computer search was undertaken with the keywords such as: work motivation; work satisfaction, teaching conditions; teacher motivation, secondary school and principal. The nature of job satisfaction was then discussed. Once the management factors that influence work satisfaction of principals were identified, they were grouped and discussed under the following headings: • factors that centres in the principal himself; • factors situated within the school; • factors at management level; • factors within the community; and • factors within the teaching career. A questionnaire was compiled from existing questionnaires (that of Hillebrand, 1989; Esterhuizen, 1989; Du Toit, 1994; Engelbrecht, 1996 and the Minnesota Importance Questionnaire, 1985). All principals at secondary schools in the Northern Cape Province, excluding schools of Correctional Services, were taken as target group in this research. The questionnaires were sent to principals within the target group. The information was statistically analized with the aid of a computer after with it was interpreted. Subsequent to these results recommendations were made. The empirical study showed that principals at secondary schools experience reasonable work satisfaction but that there are still certain factors which should be addressed. Certain recommendations are made on the basis of the empirical investigation. The most important recommendations are that the problem of work security should be addressed, rationalisation and assessment of teachers should be planned carefully and the communication between the school and the Education Department should be improved. Achievements of principals should receive more acknowledgement. === Thesis (M.Ed.)--Potchefstroom University for Christian Higher Education, 2000